Analisis Kelayakan Usahatani Kopi Robusta Di Desa Jugo Kecamatan Mojo Kabupaten Kediri - Choirina, Vifi Nurul; Maharani, Navita; Dianasari, Melinda Nur (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
In the Mojo District of East Java, the Kediri Regency Government established Jugo Village as a hub for organic coffee. There is a lot of potential for coffee plants in the region. Mojo District's Jugo Village is home to one of the centers. To enable it to thereafter produce the highest-quality plants, the district administration offers help. It is anticipated that Kediri Regency will have greater coffee potential in the future. It is hoped that robusta coffee farming operations will be able to produce high income relative to the production costs paid so that the income earned by farmers is also higher, given the potential for increasing robusta coffee farming in Jugo Village. As a result, scientists studied whether growing Robusta coffee in Jugo Village, Mojo District, Kediri Regency, would be feasible. According to study findings, the R/C ratio value of robusta coffee farming in Jugo Village, Mojo District, Kediri Regency, is more than 1. This demonstrates that the farming enterprise is profitable and viable to maintain. Keywords: Organic, Robusta Coffee, Farming Feasibility